2014
DOI: 10.1186/s13018-014-0139-7
|View full text |Cite
|
Sign up to set email alerts
|

Prospective study of superior cluneal nerve disorder as a potential cause of low back pain and leg symptoms

Abstract: BackgroundEntrapment of the superior cluneal nerve (SCN) in an osteofibrous tunnel has been reported as a cause of low back pain (LBP). However, there are few reports on the prevalence of SCN disorder and there are several reports only on favorable outcomes of treatment of SCN disorder on LBP. The purposes of this prospective study were to investigate the prevalence of SCN disorder and to characterize clinical manifestations of this clinical entity.MethodsA total of 834 patients suffering from LBP and/or leg s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
127
0
15

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(148 citation statements)
references
References 23 publications
2
127
0
15
Order By: Relevance
“…Previous work reported that entrapment of the SCN should be considered as a cause of chronic LBP or leg pain [25]. Some of the patients classified as “others” in this study may therefore have had SCN disorder.…”
Section: Discussionmentioning
confidence: 88%
“…Previous work reported that entrapment of the SCN should be considered as a cause of chronic LBP or leg pain [25]. Some of the patients classified as “others” in this study may therefore have had SCN disorder.…”
Section: Discussionmentioning
confidence: 88%
“…Trescot10 and Kuniya et al11 stated that cluneal neuralgia is not a rare clinical entity and may be underdiagnosed and should be considered as a differential diagnosis for chronic LBP or leg pain.…”
Section: Introductionmentioning
confidence: 99%
“…The etiology of low back pain (LBP) is heterogeneous and unknown in some patients with chronic pain . Superior cluneal nerve entrapment (SCN‐E) has been proposed as a causative factor; its reported incidence ranges from 1.6%–14% . The SCN derives from the cutaneous branches of the dorsal rami at T11‐L4 and innervates the skin of the upper part of the buttocks .…”
mentioning
confidence: 99%
“…1 Superior cluneal nerve entrapment (SCN-E) has been proposed as a causative factor [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] ; its reported incidence ranges from 1.6%-14%. 10,11 The SCN derives from the cutaneous branches of the dorsal rami at T11-L4 and innervates the skin of the upper part of the buttocks. [18][19][20] The nerves pass over the iliac crest through a tunnel formed by the thoracolumbar fascia and the superior rim of the iliac crest; the SCN may be compressed in this area.…”
mentioning
confidence: 99%
See 1 more Smart Citation